Internal Quality Control of Blood and Blood Components of Regional Blood Centre 9th Phitsanulok - boonjan, uraiwan; Onseng, Surachedt; Chaiyasit, Namon; Sangsorat, Nichapat; Insawang, Janejira (Health Science Clinical Research, 2023)
Abstract Objective: To analyze the results of the blood component quality test, which is an indicator of the efficiency of blood component production of the Regional Blood Centre 9th Phitsanulok, Thai Red Cross Society. Methods: This study was a retrospective study of the quality results of blood component prepared from the Regional Blood Centre 9th Phitsanulok during January to December 2021. Sampling the blood component was performed according to specific criteria depend on the type of blood component that compared the National Blood Centre, Thai Red Cross Society (NBC-TRC) standards. Data were analyzed using descriptive statistics including frequency, percentage, mean and standard deviation. Results : A total of 388 blood components (PRC, LPRC, LPPC, FFP, CRYO) were randomly examined, all blood components passed the criteria of the National Blood Center, Thai Red Cross Society 100% in all unit tests except for the leukocyte content in the LPRC and the platelet count in the LPPC with PAS, passing the criteria at 96.5% and 95.8%, respectively, from the criteria of 75%. Conclusions: The results of the randomized test on the quality of blood components produced by the Regional Blood Centre 9th Phitsanulok passed the National Blood Centre standard criteria , Thai Red Cross Society in all unit tests. This result showed that the method of producing the blood component in use was standardized and efficient. Such information may be used as a guideline for improving the quality of blood component production in Phitsanulok in the future. Moreover, this information also for users to consider correct and proper the selection of different types of blood components for patients as well. Keywords: Quality control, Red cells, Platelet, Fresh frozen plasma, Cryoprecipitate